266-nm pulse solid laser - CHEN XUGUANG; ZHANG PU; GUAN PENG; ZHAO WEI; ZHU XIANGPING; YANG JUNHONG (2021)
The invention provides a 266-nm pulse solid laser that is free of a pumping coupling system, small in size and simple in structure; picosecond pulse width fundamental frequency light can be output in a four-section bonding crystal passive Q-switching mode, and then picosecond 266-nm laser can be output; the frequency doubling conversion efficiency can be improved by focusing 1064-nm laser to perform frequency doubling and collimating 532-nm laser to perform frequency quadruplicating; the quadruplicated frequency crystal adopts a non-critical phase matching high-temperature working mode, so that the quality of a 266-nm laser beam is greatly improved, and deliquescence of the CLBO crystal is effectively prevented; the shift point design of the quadruplicated frequency crystal can effectively prolong the service life of the laser. 本发明提供的266nm脉冲固体激光器，无泵浦耦合系统，体积小、结构简单；采用四段式键合晶体被动调Q方式可输出皮秒脉宽基频光，进而可输出皮秒266nm激光；采用聚焦1064nm激光进行二倍频，准直532nm激光进行四倍频方式可提高倍频转换效率；四倍频晶体采用非临界相位匹配高温工作方式大大的提高了266nm激光光束质量，同时也有效的防止了CLBO晶体的潮解；四倍频晶体移